1998
DOI: 10.2114/jpa.17.219
|View full text |Cite
|
Sign up to set email alerts
|

Regional Differences in the Na+ Reabsorption of Sweat Glands.

Abstract: Sweat glands with a higher capacity for both sweat secretion and sodium reabsorption would contribute more effectively to thermoregulation, with less tendency to cause sodium depletion. The rate at which sweat glands reabsorb sodium and chloride does not increase proportionally as the rate of sweating increases, so that [Na + ] and [Cl -] in sweat sampled on the skin surface increase with sweating. It has been reported that there is a significant positive correlation between sweat secretory capacity and the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 7 publications
3
17
1
Order By: Relevance
“…On the other hand, the threshold of sweat rate at which sweat ion concentration increases rapidly may reflect a threshold for imbalance between production and reabsorption of ion in the sweat secretion system (a process of secretion from sweat gland to sweat duct). Thus, this threshold might reflect the capacity for ion reabsorption in the sweat duct, as it has been previously reported (Cage and Dobson 1965;Inoue et al 1998;Schwarz and Simpson 1985;Slegers 1967).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…On the other hand, the threshold of sweat rate at which sweat ion concentration increases rapidly may reflect a threshold for imbalance between production and reabsorption of ion in the sweat secretion system (a process of secretion from sweat gland to sweat duct). Thus, this threshold might reflect the capacity for ion reabsorption in the sweat duct, as it has been previously reported (Cage and Dobson 1965;Inoue et al 1998;Schwarz and Simpson 1985;Slegers 1967).…”
Section: Discussionsupporting
confidence: 56%
“…3). These relationships have not been identified in earlier studies, due to the methodological deficiencies of the previous techniques of sweat ion concentration measurement at low levels of sweating (Allan and Wilson 1971;Elizondo et al 1972;Inoue et al 1998;Tanaka et al 1992). …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The exact mechanism responsible for this is unknown; however, it has been suggested that above a certain sweat rate threshold there is insufficient time for complete sodium ion reabsorption from the duct (28). It is believed that this threshold reflects the capacity for ion reabsorption of the sweat duct (11,28). In light of the above, it is clear that changes in sweat [Na ϩ ] following heat acclimation can be misleading if they are not presented in relation to sweat rate.…”
Section: School Of Exercise and Nutritional Sciences San Diego Statementioning
confidence: 99%
“…Conventionally, filter paper, gauze pads, or commercial sweat collectors have been used to collect sweat for measurement of electrolyte concentrations (Buono et al 2007;Inoue et al 1998;Allan and Wilson 1971;Verde et al 1982;Araki et al 1981;Hamouti et al 2011). …”
Section: Introductionmentioning
confidence: 99%